Membangun Budaya Baca melalui Pojok Literasi di Lingkungan Madrasah Ibtidaiyah (MI) Darul Huda, Pandeglang - Latifah, Ella Dewi; Hasby, Rizal Maulana (IMPACT: Journal of Community Service, 2025)
Reading interest among elementary school students in Indonesia remains low, which contributes to weak literacy skills from an early age. One contributing factor is the limited availability of child-friendly reading facilities in school environments. This community service program aimed to increase students’ reading interest by providing an engaging and functional reading corner at MI Darul Huda, Ramea Village, Pandeglang Regency. The implementation method consisted of three stages: (1) preparation through school interviews and observations, as well as book collection from donors; (2) execution involving the setup of the reading corner, teacher training on literacy strategies, and student engagement activities; and (3) evaluation using qualitative observation and teacher interviews. Results indicated that 53–69% of students per class visited the reading corner daily, actively engaging in reading and book-related discussions. Teachers reported improved student interaction and reading enthusiasm. This program demonstrates that reading corners play a vital role in fostering a literacy culture in elementary schools and are suitable for replication in other schools.